Creation of a website-based information system at Mutiara Bunda Preschool using the Waterfall Method - Rendy Priyanto, Mei; Sintiawati, Bela; ismawati, adis; Andini Andriati , Dea; Laple Satria Putra, Rani (Cattleya Darmaya Fortuna, 2023)
The web-based PAUD information system is a tool for parents and school officials to assist in learning activities, both new student registration, ongoing learning activities, as well as general information such as a list of teachers and students in the scope of PAUD activities. This research uses the method waterfall in software development and testing methods with Black Box testing. In research designing information systems with a web base using the Waterfall method. The aim of this research is to improve services and information flow in terms of PAUD learning and activities and parents will find it easier to absorb information related to learning activities in PAUD. Because PAUD does not yet have a web-based information system, which is still done manually in student administration and learning activities, it is necessary to design an information system for PAUD. The results of this research will produce a website-based application, which will help parents to more easily obtain information. related to learning activities in PAUD, as well as helping teachers to manage student administration data.